(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Kidney transplantation is associated with rapid loss of bone mineral density (BMD) in the first months after transplantation. The effect of pamidronate on bone loss after transplantation was evaluated in a randomized controlled trial. Materials and Methods. Forty patients were enrolled in this study (16 in the pamidronate group and 24 in the control group). Pamidrinate was administered as 30-mg intravenous infusion within 2 days after transplantation and 3 months later. All of the patients received calcium and vitamin D supplementation. Laboratory parameters and BMD (lumbar spine and femoral neck) were measured at baseline and 6 months after kidney transplantation. Results. Bone mineral density at the initiation of study had no significant differences between the two groups. In each group, BMD of femoral neck and lumbar spine had no significant differences 6 months after transplantation in comparison to pretransplantation values. There was no significant difference in BMD changes after intervention between two groups. Parathyroid hormone level normalized in both of the pamidronate and control groups 6 months after kidney transplantation. Glomerular filtration rate at the end of study was not significantly different between the two groups. Conclusions. Our study suggests that administration of calcium and vitamin D following transplantation may be beneficial to counterbalance the substantial bone loss occurring within 6 months after transplantation, and addition of pamidronate has no beneficial effect in BMD in this short interval after kidney transplantation.